THE PROBLEMS THAT ARISE IN THE FORMATION OF STUDENTS’ WRITING SKILLS IN ENGLISH - Alijonova Sarvinoz Azizbek qizi; Ahmedova Matluba Ibgragimjonovna (Ta’limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2023)
Anotation: The formation of students' writing skills in English can pose several challenges that need to be addressed. As English becomes more prevalent in global communication, the importance of strong writing skills cannot be overstated. However, students often face obstacles that hinder their development in this area. Identifying and addressing these problems is crucial for facilitating students' growth as proficient writers in English.